Domestic Violence in Rural Haryana: Issues and Challenges: Understanding and Addressing Domestic Violence in Rural Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Domestic Violence is global phenomena and one of the central issues for contemporary women’s movements. Not only has domestic violence been acknowledged worldwide as a violation of basic human rights of women, but an increasing amount of research highlights the health aspect, inter generation effect and demographic consequence of such violence. The abuse of women by men is among the most common and dangerous forms of gender based violence. For women, violence is a phenomenon which starts at conception and carries on through their entire life span. In India, Pre-birth selection and consequent infanticide is a common occurrence and the preference for a male offspring widespread. Discrimination continues by way of access to adequate food, prompt medical facilities, burden of housework, care of siblings and so on leading to lack of education and consequent lack of awareness and empowerment and imparting of skills. Domestic violence is violent victimization of women, within the boundaries of family usually by men or his family to whom they are married or with whom they have marriage like relationship. Domestic Violence can be physical, sexual, economic, and psychological. Generally, an important part or power relationship between spouses and their families relates to dowry and its ramifications. The present study was conducted in rural Haryana with a view to understand the various forms of violence prevalent in rural society and their impact on women. It was observed that across cast and class lines women suffer from different forms of violence.